Temporal trends in dioxin-like polychlorinated biphenyl concentrations in serum from the general population of Shandong Province, China: A longitudinal study from 2011 to 2017. (December 2018) - Lin, Mu; Ma, Yulong; Yuan, Haodong; Luo, Xinghua; Wang, Qinghua; Liu, Anming; Wang, Ying; Jin, Jun
Abstract: Temporal changes in the concentrations of dioxin-like (DL) polychlorinated biphenyls (PCBs) in environmental and biological matrices in China are not well understood. We determined the DL-PCB concentrations in pooled serum samples from the general population of Weifang City, Shandong Province, China in 2011 (n = 305) and 2017 (n = 495). The total DL-PCB concentration was 3.48 ± 1.31 ng/g lipid (mean ± standard deviation) in 2011 and 2.82 ± 1.73 ng/g lipid (19% lower) in 2017, but the difference was not statistically significant (p = 0.347). The DL-PCB concentrations and toxic equivalent concentrations were much lower in the serum from Weifang residents than have been found in serum from the inhabitants of other parts of the world. The concentrations of most of the DL-PCB congeners followed different downward temporal trends, but the PCB-118 concentration was higher in 2017 than in 2011. The temporal changes in the PCB concentrations and compositions in the samples from the general population of Weifang indicated that there may a new source of unintentionally produced PCBs in Weifang. Graphical abstract: Image 1 Highlights: The total DL-PCB concentrations were higher in the samples from people aged 50–59 and ≥60 y than the younger people. The DL-PCB concentrations were lower in the samples collected in 2017 than in the samples collected in 2011. Except PCB-118, the concentrations of most of the DL-PCB congeners followed different downward temporal trends.